Efektifitas plester berbahan ekstrak kunyit dan nacl dalam penyembuhan luka bakar grade ii pada tikus putih (rattus norvegius) - Andrayani, Lale Wisnu; Rusmini, Rusmini; Emilyani, Desty; Kurnia, Theresia Avila (Jurnal Keperawatan Muhammadiyah, 2024)
Burns are one type of wound in which tissue damage occurs due to contact with heat sources such as water, hot fire (liquid), electrical chemicals and radiation. Wound care with natural ingredients has been widely used by the community traditionally. One of the most widely used plants is turmeric, turmeric is used as an anti-inflammatory, anti-irritant antiseptic, anorexia medicine for wounds and liver disorders. Turmeric contains the compound curcumin (Curcuma domestica Val) which can accelerate reepithelialization, cell proliferation, and collagen synthesis. The purpose of this study was to determine the effectiveness of turmeric extract on wound healing in grade II burns. This study is a true experimental type of research with a post only test design with control group design which will use two groups, namely the treatment group who will be given wound care with turmeric extract and the control group who will be given standard wound care with NaCl compresses. The results showed that the wound granulated 7 days faster than the control group. The results of statistical tests using Man Whitney showed a significant difference in the duration of granulation wounds in the two groups (p = 0.002 < 0.05). The results showed that the epithelial wound was 7 days faster than the control group. The results of statistical tests using Man Whitney showed that there was a significant difference in the length of the epithelial wound in the two groups (p = 0.018 < 0.05). The results showed that there was no significant difference in the duration of wound reorganization in the turmeric extract plaster and NaCl plaster group (p=0.988 > 0.05). The conclusion in this study was that there was a significant difference in the length of the wound to granulate and epithelialize, but in tissue reorganization, the results were not significant between turmeric extract and NaCl.